NAVIGATING ORGANIZATIONAL CRISES AND UNCERTAINTIES THROUGH WEB AUGMENTED REALITY (WebAR) - Jeganathan, Kishokanth (Management and Administration Journal, 2024)
Web Augmented Reality (WebAR) has emerged as a pivotal component within the paradigm of Industry 4.0 technologies. Its proliferation across diverse sectors underscores its potential as a transformative tool, particularly in the context of organizational micro-environments. Unlike traditional Augmented Reality (AR) platforms, which often necessitate substantial financial and technical investments, WebAR offers a more cost-effective and accessible alternative. Despite its apparent advantages, the adoption rate of WebAR remains relatively subdued. This article aims to undertake a rigorous theoretical examination of WebAR’s capacity to address and mitigate crises and uncer-tainties inherent within organizational micro-environments. To this end, the paper will review WebAR, engage in a comparative analysis between WebAR and its traditional AR counterparts, highlighting the distinctive attributes and potential advantages of the former, and delve into the theoretical implications of WebAR’s utility in navigating orga-nizational crises and uncertainties, drawing from relevant academic literature and theoretical frameworks. By adop-ting a more abstract and theoretical lens, this paper seeks to contribute to the body of knowledge surrounding WebAR. It aspires to foster a deeper academic understanding of its potential applications and implications, eschewing a more pragmatic approach in favor of a comprehensive theoretical exploration.